Anti-Obesity Effect of Ethanolic Extract of Citrus Paradisi and Naringin in HFDInduced Animal Model: Life Sciences -Biochemistry - R. Roghini, Dr. (International Journal of Life Science and Pharma Research, 2023)
The study aimed to assess the effectiveness of Citrus paradisi, and Naringin on high fat diet rats.It must be clarified thatthe correlation between body fat and dietary fat levels, long-term energy intake and expenditure imbalances causes Obesity. Animalmodels have made a significant historical contribution to our understanding of the underlying variables that control the elementsof human energy balance. studies have shown that genetics considerably affect how the body reacts to meals high in fat-derivedenergy. Five sets of six male Wistar rats (120–150g); each group had five animals. Group I (Control), Group II (High Fat Diet),Group III (HFD+Naringin (100mg/kg body weight)), Group IV (HFD + Citrus paradise (500mg/kg body weight), and Group V (HFD+21.67mg/kg body weight) are the study groups (drug control). Physical factors such as body weight, organ weight, fat pad weight,and anthropometric parameters were assessed after introducing a high-fat diet. In addition, serum lipid profiles, glucose, insulin,leptin, and adiponectin levels, among other biochemical indicators, were analyzed. These outcomes would empower Citrus Paradiseand Naringin to be utilized as anti-obesity agents. Haemotoxylin and eosin staining was used to detect histopathological alterationsin adipose tissue. The effect of Citrus paradisi and Naringin treated with HFD-induced animals showed significantly higher (p<0.001*).It was observed by its action in reducing organ weight, blood weight, and serum lipids. This current study evaluated the evidencefor Citrus Paradise’s effects on body weight, blood pressure, and lipid profile.